G208 Emergency Department attendance by patients aged 0–15 years following contact with the NHS 111 telephone advice service: Analysis of linked data from hospitals, GP Out of Hours and NHS 111. (27th April 2016) - Robinson, C; Wolters, AT; Steventon, A; Pope, R; Hargreaves, D; Maconochie, I
Abstract : Concerns have been raised that some referrals from NHS 111 to Emergency Departments (EDs) for children are unnecessary; increasing pressure on services whilst some appropriate cases are not being referred. This paper's aim is to analyse what factors were associated with ED attendances after parents/carers call NHS 111. We studied 32, 398 NHS 111 calls made between April 2013 and February 2015 for children aged under 16 in the area covered by three Clinical Commissioning Groups. We used logistic regression on linked NHS 111, EDs and GP Out-Of-Hours (GPOOH) data to test predictors of ED attendance within five hours following NHS 111 contact. The data included patient characteristics (e.g. age, symptom), call characteristics (e.g. time of call) and wider contextual characteristics. Of the patients studied, 13.1% were advised to go to ED[1] and 9.3% visited ED. There was a mismatch between advice and actual attendance: 8.1% of all patients studied were advised to attend ED but did not and 4.3% were not advised to attend but did so anyway. The symptom that patients presented was an important factor in this (see Figures 1 and 2). We found, using the logistic regression results, distance from an A&E department strongly affected whether patients attended ED; patients were roughly half as likely to attend for every kilometre further away. GP patient satisfaction rating and office hours, also affected the patient's likelihood of attending ED (see Table 1 ). Advice given was more risk averse in recommending ED attendance than the behaviour of patients with injuries, limb problems and burns. In contrast, call handlers did not seem to assuage the parents' concern regarding other symptoms such as fever. A limitation of this study is that we could not assess the proportion of children whose symptoms changed after the call and that appropriateness of the ED attendance or lack of attendance cannot be assessed. [1] 3.7% were advised by GPOOH and 9.3% were advised by NHS 111. Patients are frequently redirected to GPOOH service by NHS 111 whilst on the line. Patients make little distinction between the services.